Reduced length of nodes of Ranvier and altered proteoglycan immunoreactivity in prefrontal white matter in major depressive disorder and chronically stressed rats - Miguel-Hidalgo, José Javier; Hearn, Erik; Moulana, Mohadetheh; Saleem, Khunsa; Clark, Austin; Holmes, Maggie; Wadhwa, Kashish; Kelly, Isabella; Stockmeier, Craig Allen; Rajkowska, Grazyna (Scientific reports, 2023)
Major depressive disorder (MDD) and chronic unpredictable stress (CUS) in animals feature comparable cellular and molecular disturbances that involve neurons and glial cells in gray and white matter (WM) in prefrontal brain areas. These same areas demonstrate disturbed connectivity with other brain regions in MDD and stress-related disorders. Functional connectivity ultimately depends on signal propagation along WM myelinated axons, and thus on the integrity of nodes of Ranvier (NRs) and their environment. Various glia-derived proteoglycans interact with NR axonal proteins to sustain NR function. It is unclear whether NR length and the content of associated proteoglycans is altered in prefrontal cortex (PFC) WM of human subjects with MDD and in experimentally stressed animals. The length of WM NRs in histological sections from the PFC of 10 controls and 10 MDD subjects, and from the PFC of control and CUS rats was measured. In addition, in WM of the same brain region, five proteoglycans, tenascin-R and NR protein neurofascin were immunostained or their levels measured with western blots. Analysis of covariance and t-tests were used for group comparisons. There was dramatic reduction of NR length in PFC WM in both MDD and CUS rats. Proteoglycan BRAL1 immunostaining was reduced at NRs and in overall WM of MDD subjects, as was versican in overall WM. Phosphacan immunostaining and levels were increased in both in MDD and CUS. Neurofascin immunostaining at NRs and in overall WM was significantly increased in MDD. Reduced length of NRs and increased phosphacan and neurocan in MDD and stressed animals suggest that morphological and proteoglycan changes at NRs in depression may be related to stress exposure and contribute to connectivity alterations. However, differences between MDD and CUS for some NR related markers may point to other mechanisms affecting the structure and function of NRs in MDD.